Perilaku Kecanduan Judi Online Pada Mahasiswa: Analisis Perspektif Pengelolaan Keuangan Pribadi - Luluk Nurlaila; Tri Wahyuni; Rauly Sijabat (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
The rapid development of digital technology has brought significant changes to various aspects of student life, including the emergence of online gambling as a concerning social phenomenon. This research aims to understand the behavior of students involved in online gambling and its impact on personal financial management. Using a qualitative descriptive approach with in-depth interviews, this study involved one active student informant who had experienced online gambling addiction. The results showed that students became acquainted with online gambling through their social environment, particularly friendships in boarding houses. Initial motivation was driven by curiosity, but winning experiences reinforced gambling behavior. High intensity and duration of play indicated loss of control, which is a characteristic of addiction. Online gambling had multidimensional impacts including academic disruption, financial problems, social conflicts, and psychological pressure. The findings are consistent with Personal Financial Management Theory which states that the inability to manage finances can lead to irrational and risky financial decisions